Biography : WWE legends. Volume 2 [videorecording (DVD)] - Michaels, Shawn; Ultimate Warrior, 1959-2014; Foley, Mick; Hart, Bret; Abramson, Brad; Amigone, Daniel; Chase, Matthew; Cocuzza, Anthony; De Groot, Stephen; Frontain-Bryant, Elaine; Hehr, Jason; Kaiser, Chris; et al. (Biography (A & E Home Video (Firm)), 2021)
Get ready to rumble with BIOGRAPHY: WWE LEGENDS, VOLUME 2 from A & E Network and WWE Studios. This collection of documentaries pulls back the curtain on the twists, turns, and triumphs on the paths to fame and icon status for these WWE Legends. Helmed by some of the industry's top directors and storytellers, these programs reveal that there is more than meets the eye in the over-the-top athleticism and alter-ego swagger of Shawn Michaels®, Ultimate Warrior, Mick Foley, and Bret "The Hitman" Hart